2012
DOI: 10.1262/jrd.2011-035
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Body Weight and Milk Yield During the Early Postpartum Period and Bull and Technician and the Reproductive Performance of High Producing Dairy Cows

Abstract: Abstract. The aim of this study was to evaluate the effect of body weight (BW) change during the early postpartum period and BW on day 50 post partum on the subsequent expression of estrus and fertility at first insemination before day 90 post partum. The data were derived from 1036 postpartum cows reaching 90 days in milk. The following data were recorded for each animal: lactation number, daily milk production at day 50 post partum, calving date, days in milk at estrus and at AI, insemination date, inseminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…Cows suffering from metritis were randomly allocated to one of the two groups according to the last digit of their ear tag. Thus, cows with an odd number (1,3,5,7,9) were allocated to the P group. In this group, cows only received parenteral amoxicillin by intramuscular route.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Cows suffering from metritis were randomly allocated to one of the two groups according to the last digit of their ear tag. Thus, cows with an odd number (1,3,5,7,9) were allocated to the P group. In this group, cows only received parenteral amoxicillin by intramuscular route.…”
Section: Experimental Designmentioning
confidence: 99%
“…The reproductive performance of a cow after parturition is affected by many factors such as parity, the number of days without milk production, body weight (BW) loss, heat stress, season at the first artificial insemination (AI), season at conception, bull used for the AI, and the technician who carries out the AI [1]. Moreover, clinical conditions such as clinical ketosis, clinical hypocalcemia, and uterine diseases could negatively affect the future reproductive performance of the cow [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…But some authors have associated increases in milk yield with decreases in pregnancy ratio (Santolaria et al, 2012). Roche (2006) stated that high-producing cows have a greater negative energy balance (NEB) and its magnitude is directly related to reproductive failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, this could be considered a confounder because all AITs were required to attend at least one training before practicing AI. Studies have shown that participation in refresher courses can lead to higher AI success rates [13,14,17,18]. Moreover, statistical significance was found between training in PCC Ubay and AI success rate.…”
Section: Resultsmentioning
confidence: 95%
“…This is contrary to the findings of Cembrowics [16] where the number of inseminations did not affect the success of AI. However, a high number of inseminations can be associated with better familiarity of the reproductive system [11] and higher confidence of the technician [17] leading to higher success rates.…”
Section: Resultsmentioning
confidence: 99%